The Effect of Thyroid Dysfunction on the Cardiovascular Risk of Type 2 Diabetes Mellitus Patients in Ghana - Osei Sarfo-Kantanka; Fred Stephen Sarfo; Eunice Oparebea Ansah; Ishmael Kyei (Journal of Diabetes Research)
Background. Thyroid dysfunction is known to exaggerate the coronary heart disease (CHD) risk associated with type 2 diabetes mellitus (T2DM) among whites. The effect is yet to be studied among African populations. Methods. This is a cross-sectional study involving 780 T2DM patients enrolled in a diabetes clinic in Kumasi, Ghana. CHD risk was estimated using the Framingham and UKPDS risk scores. Risks were categorised as low (<10%), intermediate (10–19%), and high (≥20%). Associations between metabolic risk factors, thyroid dysfunction, and CHD risk were measured using Spearman’s partial correlation analysis while controlling for age and gender. Differences were considered statistically significant at p<0.05. Results. 780 T2DM patients (57.7% females), mean ± SD age of 57.4 ± 9.4 was analysed. The median (IQR) 10-year CHD score estimated using the Framingham and UKPDS risk engines for males and females was 12 (8–20), 9.4 (5.7–13.4), p<0.0001 and 3 (1–6), 5.8 (3.4–9.6), p<0.0001, respectively. Positive correlation was found between CHD risk and HbA1c, total cholesterol, low-density lipoprotein cholesterol, systolic blood pressure, and thyroid stimulating hormone. Conclusion. The presence of thyroid dysfunction significantly increased the CHD risk associated with T2DM patients in Ghana.